MAINTAINABILITY INDUSTRY PREVENTING OCCUPATIONAL ACCIDENTS AND INCREASE PRODUCTION - Gempur Santoso, (International Journal of Social Science, 2023)
Labor and all equipment really need to be saved by being treated. That industrial management must have a deep commitmentmaintenance. So that production can run smoothly and optimally. The design of scientific writing uses descriptive. Data collection method is done by using literature study. Data analysis uses descriptive, analyzing various findings or opinions from various literature aboutmaintenance, work accidents, and product improvement. The inference method uses deductive. Conclusion,thatmaintenanceis to save the equipment and workforce of the factory/industry community so that they remain in the initial conditions of production operations, it is necessaryaccident preventiontaking into account several factors, namely: a. factory environmental factors, b. equipment and work equipment factor, c. energy management factors have a risk of danger, and d. human factor. Suggestions, industrial management must have a commitment to rescue (maintenance) on products, maintenance of work tools/equipment, work environment and workforce in the industry.